Ailanthus excelsa leaf extract: Chemical characterization, antischistosomal activity, and in silico study of isolated phenolic compounds as promising thioredoxin glutathione reductase inhibitors - Hala Sh. Mohammed, Samia William, Tarek Aboushousha, Hoda M. Abu Taleb, Rehab Sabour, Mosad A. Ghareeb (Journal of Applied Pharmaceutical Science, 2023)
Hepatic schistosomiasis is the most well-known chronic condition, with a variety of clinical symptoms. In the current study, the metabolite profile of the Ailanthus excelsa leaf butanol extract was investigated using chromatographic isolation and Liquid chromatography-electrospray ionization /mass spectrometry (LC-ESI-MS/MS) analysis. Also, its schistosomicidal effect was examined in vivo regarding disease progression in a comparative experimental study to praziquantel (PZQ). The parasitological parameters (total worm burden, tissue egg load, and oogram pattern) of the infected and the treated mice were counted. A histopathological examination of the liver granuloma took place as well. The extract (at a dose of 500 mg/kg) caused a significant worm reduction of 41.30% and also a significant reduction in intestinal egg load (6.36 ± 1.12 vs. 17.82 ± 2,024.6). Data also showed a reduction in immature eggs in the extract group (33.00 ± 2.45 vs. 57.4 ± 3.89) when compared to the infected untreated group. Five phenolic compounds were isolated and identified as gallic acid (1), methyl gallate (2), quercitrin (3), isoquercitrin (4), and kaempferin (5). Furthermore, molecular docking was utilized for the first time to evaluate the efficacy of the isolated compounds (1–5) in disrupting the essential worm enzyme thioredoxin glutathione reductase. Compounds 3–5 showed high docking scores ranging from −7.054 to −11.370 kcal/mol that were comparable to that of PZQ (−6.407 kcal/mol). Moreover, LC-ESI-MS/MS profiling led to the identification of 33 secondary metabolites. These compounds were classified as phenolic acids, flavonoids, iridoids, stilbenoids, chalcones, tannins, and coumarins. The findings suggest that the A. excelsa leaf extract could be used as a naturally occurring antischistosomal agent and this emphasizes the significance of phenolic components.